Забезпечення економічної безпеки транспортних підприємств в умовах фінансової нестабільності - Бобиль, Володимир Володимирович; Дехтяр, Сергій Сергійович (ТОВ «ДКС Центр», Київ, 2022)
UKR: У сучасних умовах транспортні підприємства, як і будь-які інші, вимушені адаптуватися до умов політичної, соціально-економічної та фінансової нестабільності, постійно вирішуючи різні проблеми, та шукати шляхи зниження загроз власному існуванню. Високий моральний і фізичний знос сновних засобів, обмеженість фінансових ресурсів, недостатність власних оборотних коштів, порушення бізнес-зав’язків призводять до порушень у господарській діяльності транспортних підприємств. Як наслідок виникає необхідність створення та реалізації механізму забезпечення їх економічної безпеки, що допоможе знизити рівень загроз та втрат, особливо в умовах фінансової нестабільності. У науковій роботі визначено критерії оцінки ризиків транспортних підприємств та обґрунтовано систему управління ризиками для забезпечення економічної безпеки транспортних підприємств в умовах фінансової нестабільності.

ENG: Nowadays, transport companies are forced to carry out their activities in conditions of financial instability, globalization and a changing external environment. Adaptation to this requires the enterprise to form a certain potential of resources to ensure its development. This process requires significant investments, which are always associated with threats and risks. In this situation, the protection of the transport enterprise from internal and external threats affecting the level of the enterprise's economic potential means its economic security both in a stable economic environment and in periods of crisis. The difference is only in thedetermination of the tasks that the enterprise faces in one or another period. One of the key tasks in conditions of financial instability is the systematization of risks, which can be defined as the search for forms of prevention, elimination or overcoming risks in conditions of financial instability. Modern business conditions are characterized by a complex multi-level structure, which creates risks of a multifaceted nature. The degree of economic security of transport enterprises can be characterized by its ability to withstand threats and eliminate losses from the influence of negative environmental factors. In this context, the threat of economic security can be understood as the real or potential effects of legal entities and/or individuals that violate the safe condition of transport enterprises and may lead to financial or other losses, as well as to the termination of their activities. The risk in the field of ensuring the economic security of a transport enterprise should be defined as the probability of harming its economic interests based on the realization of a threat to its economic security. The presence of risk in economic activity means that in order to achieve the set goals, the enterprise needs to develop plans for its development, taking into account the probabilistic nature of the origin of events. For any transport enterprise, the study and assessment of risks is necessary in order to determine the occurrence of events with negative consequences, as well as the danger of unexpected losses, damages and underachievement of profits compared to the planned. The scientific work defines the criteria for assessing the risks of transport enterprises and substantiates the risk management system to ensure the economic security of transport enterprises in conditions of financial instability.
Ensuring the Economic Security of Transport Enterprises in Conditions of Financial Instability
В. Бобиль: ORCID 0000-0002-7306-3905; С. Дехтяр: ORCID 0000-0002-5513-336
Keywords: економічна безпека; ризик; підприємства транспорту; фінансова нестабільність; ризик-менеджмент; economic security; risk; transport enterprises; financial instability; risk management; КФОП